Application of Audiovisual Resources in University Students in Rural Areas - Salazar-Palomino, Sandra; Huamán Romaní, Yersi Luis; Szczcpansky-Grobas, David; Alarcón-Sucasaca , Aldo (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
The preference for paper-based learning (traditional) or audio-visual learning (electronic) brought about hybrid learning whose preference among students is much greater due to the interaction with digital and audio-visual media. The general objective is to analyze and describe the experiences of university students on paper-based learning called traditional and audio-visual learning called e-learning, for which a quantitative descriptive and correlational methodology was used with a measurement instrument through an anonymous and voluntary survey with 1240 participants. The results have acceptable statistics and are demonstrated with the confirmatory factor analysis, showing the preference for hybrid learning. Conclusion, students request that universities implement this methodology (hybrid) to work properly and have a quality education in the future